2019
DOI: 10.1111/jan.13980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a mHealth programme on coronary heart disease prevention among working population in Singapore: A single group pretest–post‐test design

Abstract: Aim:The aim of this study was to develop and examine the effectiveness of a 4-week Mobile Health (mHealth) programme using the smartphone app Care4Heart on awareness, knowledge, perceived stress, and a heart-related lifestyle among working population in Singapore. Design:A quasi-experimental single group pretest and repeated post-test design.Methods: A total of 160 nonhealth-related working adults were recruited from February 2016-April 2016. The Care4Heart app was installed on the participants' phones. Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…A similar study from Singapore that targeted coronary heart disease prevention via an app measured risk awareness, knowledge of risk factors, perceived stress levels, and heart-related lifestyle measures as outcomes [ 91 ]. Jiang et al [ 91 ] concluded that the intervention increased risk awareness and disease knowledge and the effects persisted for at least 6 months. They did not measure disease risk or incidence as outcomes [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study from Singapore that targeted coronary heart disease prevention via an app measured risk awareness, knowledge of risk factors, perceived stress levels, and heart-related lifestyle measures as outcomes [ 91 ]. Jiang et al [ 91 ] concluded that the intervention increased risk awareness and disease knowledge and the effects persisted for at least 6 months. They did not measure disease risk or incidence as outcomes [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, researchers only addressed one or two health outcomes in a single study, such as medication compliance, exercise, weight loss, LDL‐C control, health education, or psychology (Jiang et al, 2019; Lu et al, 2020; Mellwig et al, 2017; Pedersen et al, 2019; Pogosova et al, 2019; Zou et al, 2021). However, in our study, six primary outcomes and three secondary outcomes were verified according to the “ABCDE” strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, CHD patients often have negative emotions such as anxiety, and poor self-efficacy. Jiang Ying et al have found that the self-management ability and nursing compliance of such patients decrease with the passage of time after discharge [ 7 , 8 ]. Therefore, strong external intervention measures are required.…”
Section: Introductionmentioning
confidence: 99%